Pengaruh Kompetensi SDM dan Modal Finansial Terhadap Kinerja Usaha Kerajinan Sulaman di Desa Naras - Febbyo Millendra; Marwan Marwan (Universitas Negeri Padang, 2022)
The purpose of this study is how HR competence and financial capital affect performance of handicraft business. Type of research is referred to as causal comparative research. A field survey with a questionnaire was used to collect data in this study. This study included a total population of 40 participants. The sample technique employed was the area cluster sampling technique, that is a region-based sampling. According to the result of the research, (1) HR competency has a favorable impact on the performance of Naras Village's handicraft business. (2) Financial capital has a positive impact on performance of Naras Village's handicraft business. (3) In the village of Naras, HR competence and financial capital have a positive impact on the performance of the craft business.